(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
This article is focused on presenting a fast road to the main Lean Startup method principles. It also establishes a 14 norms manifesto that suggests possible questions to take into account in order to be successful by acquiring viability and scalability in technology based business models.